Calculation of expected credit risks according to the IFRS9 standard and its implications in the volume of credit by application at the National Bank of Iraq (Entrepreneurship Journal for Finance and Business, 2023)
The research focuses on calculating the expected credit risks according to the IFRS9 9 standard and how to apply this standard in the National Bank of Iraq. IFRS9 9 is an accounting standard that deals with the classification, financial value of financial assets and the management of risks related to them. Modern accounting standards require considering the financial risks of loans and other financial products owned by the bank. The IFRS9 9 standard aims to supply a comprehensive credit risk management system and supply a probable estimate of expected losses on loans and other financial products. The process of calculating the expected credit risk by the IFRS9 9 standard includes several main steps. First, financial products should be classified according to the degree of expected risk. This classification is based on the quantitative and qualitative information relevant to the bank and the credit risk assessment for each category. After that, the expected credit size for each category is decided based on forecasting models and risk estimates. These models are based on a set of accounting, economic and business standards. Historical data and current information are used to decide the expected credit volume and the possible risks entailed by financial portfolios. According to accounting standards, banks must include the expected credit volume in periodic financial reports and constantly update it. This helps third parties, such as investors and regulators, to understand the bank's exposure to credit risks and the efficiency of the bank's risk management. This process is reflected in the volume of credit applied at the National Bank of Iraq by improving the bank's understanding of credit risks and thus the ability to make better decisions in granting loans and managing risks. The aim of this research is to study the calculation of expected credit risks following the IFRS9 9 standard and analyze their impact on the credit volume in its application at the National Bank of Iraq. The focus is on understanding the details of the standard and how to apply it to improve risk management and make better decisions in granting loans. Through this research, we have concluded that calculating the expected credit risks by IFRS9 contributes to enhancing the bank's understanding of credit risks and improving its efficiency in risk management, and the correct application of the standard helps in supplying more transparent and predictable financial reporting of potential losses. Based on the findings, there are some recommendations for improving risk management at the National Bank of Iraq and applying the IFRS9 standard. The bank should strengthen its technical capabilities to collect and analyze financial data and credit ratings in a more correct and effective manner, and the bank should supply continuous training to employees on the standard and methods of its implementation and the use of proper predictive models to calculate the expected credit risks. Finally, the bank should give financial reports in an organized and transparent manner, explaining the expected credit volume and the potential risks entailed by this volume. This will help investors and regulators understand the extent of the bank's exposure to credit risks and the efficiency of the bank's risk management.